Establishment of Serum GOT & GPT in Pregnant Women Through trimesters in holly Al- Najaf Governorate - Al-Shammary, Dr. Sanna Abadi Habeab (University of Thi-Qar Journal, 2019)
The search of a new parameters for monitoring and even pregnant women are still an impartment issue in many research fields. Some studies focused on the role of Glutamate Oxaloacetate Transferase (GOT) status, while others concentrated on Glutamate Pyruvate Transaminase( GPT) disturbances or even stress disorders of liver function. This study was conducted on randomly selected 70 pregnant women attending in Al-Zahra hospital for delivery in Al- Najaf province. The subject were divided into three main Trimester groups: 1st Trimester group(10 pregnant women).2nd Trimester group (20 pregnant women) & 3ed Trimester group :( 20 pregnant women)and Control group ( 20 non pregnant women). The study was carried out from 1/7/ 2013 – 1/4/2014.The age of subject and control groups were range of 15-45years.The results show significant increase (p? 0.05) for concentration of both GOT&GPT in 2nd trimester in subjects as compared with control group and same groups. Also there was a relationship between age and enzyme activity.